INDEKS KEPUASAN MASYARAKAT ATAS PELAYANAN PUSKESMAS TERAKREDITASI MADYA DI KABUPATEN KUBU RAYA PROVINSI KALIMANTAN BARAT - Pardi, Pardi (Jurnal Bisnis Indonesia, 2019)
This study aims to determine the extent of community satisfaction with the services provided by the Middle Accredited Puskesmas in Kuburaya Regency, West Kalimantan Province, namely Puskesmas,Sungai Durian, Puskesmas Sungai Raya Dalam and Puskesmas Sungai Kakap. The research method used in this research is descriptive statistics which illustrates the results of descriptive statistical analysis by measuring the Community Satisfaction Index that is looking for IKM Value and then comparing the results of the IKM value with the criteria determined according to Kepmenpan RB of 2009. Data collection using survey methods with tools help in the form of a questionnaire, with a score of 1 to 4 Likert scale. The results of this study indicate that the three Middle Accredited Puskesmas are generally rated by service users as being good in providing services in Puskesmas. But the value of each Puskesmas is different for each of the nine elements assessed. The perceived value is still low by users of the Puskesmas services related to service requirements and procedures. While the highest value related to the nine service elements is the clarity and certainty of service and the friendliness of the officers in providing services. In general, the three Puskesmas are based on the IKM Value of Puskesmas Sungai Durian 75.75, Puskesmas Sungai Raya Dalam at 73.75 and Puskesmas Sungai Kakap at 70.25, all of which are in the range of 62.51 - 81.25 meaning that the criteria are good in providing services to service users. The recommendations for the three Puskesmas are to be able to improve services on service elements that are still considered low by service users by eliminating unnecessary requirements and shortening service procedures without reducing service quality. Keywords: Services, Middle Accredited Puskesmas, Satisfaction Index Society (IKM)